The Sculptor - Mccloud, Scott (New York Roaring Brook Press, 2015)
David Smith is giving his life for his art—literally. Thanks to a deal with Death, the young sculptor gets his childhood wish: to sculpt anything he can imagine with his bare hands. But now that he only has 200 days to live, deciding  what  to create is harder than he thought, and discovering the love of his life at the 11th hour isn't making it any easier!

This is a story of desire taken to the edge of reason and beyond; of the frantic, clumsy dance steps of young love; and a gorgeous, street-level portrait of the world's greatest city. It's about the small, warm, human moments of everyday life…and the great surging forces that lie just under the surface. Scott McCloud wrote the book on how comics work; now he vaults into great fiction with a breathtaking, funny, and unforgettable new work.